Δ15N values in plants are determined by both nitrate assimilation and circulation. Issue 6 (14th March 2020) - Cui, Jing; Lamade, Emmanuelle; Fourel, François; Tcherkez, Guillaume
Summary: Nitrogen (N) assimilation is associated with 14 N/ 15 N fractionation such that plant tissues are generally 15 N‐depleted compared to source nitrate. In addition to nitrate concentration, the δ 15 N value in plants is also influenced by isotopic heterogeneity amongst organs and metabolites. However, our current understanding of δ 15 N values in nitrate is limited by the relatively small number of compound‐specific data. We extensively measured δ 15 N in nitrate at different time points, in sunflower and oil palm grown at fixed nitrate concentration, with nitrate circulation being varied using potassium (K) conditions and waterlogging. There were strong interorgan δ 15 N differences for contrasting situations between the two species, and a high 15 N‐enrichment in root nitrate. Modelling shows that this 15 N‐enrichment can be explained by nitrate circulation and compartmentalisation whereby despite a numerically small flux value, the backflow of nitrate to roots via the phloem can lead to a c. 30‰ difference between leaves and roots. Accordingly, waterlogging and low K conditions, which down‐regulate sap circulation, cause a decrease in the leaf‐to‐root isotopic difference. Our study thus suggests that plant δ 15 N can be used as a natural tracer of N fluxes between organs and highlights the potential importance of δ 15 N of circulating phloem nitrate.